Studies on Protease from Aspergillus Aculeatus - Elegbe, Isaac Anuolowapo (Obafemi Awolowo University, 2014)
Aspergillus aculeatus associated with the black tongue disease was able to grow in liquid synthetic medium. Growth was maximum on the fifth day of incubation. Growth was optimum at pH 6.5 and 35 °c. The best carbon source for growth was glucose while among the nitrogen sources used, optimum growth occurred on tryptone. During growth of A. aculeatus in liquid synthetic medium, proteins were released and proteolytic activity was detected. Proteolytic activity was optimum when the sole carbon and nitrogen sources were galactose (or inositol) and peptone respectively.